2013
DOI: 10.1021/ja4072145
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Stereocontrol Elements of a Catalytic Asymmetric Chlorolactonization: Syn Addition Obviates Bridging Chloronium

Abstract: We report absolute and relative stereochemistry of addition in enantioselective chlorolactonizations of 4-phenyl-4-pentenoic acid and its related t-butyl ester, catalyzed by (DHQD)2PHAL. Predominant syn addition of the chlorenium and the nucleophile across the olefin is observed. As shown by isotopic labeling, NMR spectroscopy, and derivative studies, the two new stereocenters formed by addition across the double bond are set independently and influenced by different factors. These findings suggest a stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…24 It was concluded that the reaction operates via an open tertiary carbocation intermediate which then undergoes ring closing under the stereocontrol of the catalyst. This mechanism of operation explains the lack of selectivity for 1,2-disubstituted olefinic acids in the chlorolactonization with cinchona-based catalysts; these substrates should form less stable secondary carbocations and would be more prone to be captured as chloriranium ions or tight ion pairs in an anti addition process.…”
Section: Introductionmentioning
confidence: 99%
“…24 It was concluded that the reaction operates via an open tertiary carbocation intermediate which then undergoes ring closing under the stereocontrol of the catalyst. This mechanism of operation explains the lack of selectivity for 1,2-disubstituted olefinic acids in the chlorolactonization with cinchona-based catalysts; these substrates should form less stable secondary carbocations and would be more prone to be captured as chloriranium ions or tight ion pairs in an anti addition process.…”
Section: Introductionmentioning
confidence: 99%
“…[2] They have also provided evidence, in some cases, for a concerted mechanism in these reactions; while in other cases, formation of a carbocation intermediate was found to be favored. [24] …”
mentioning
confidence: 99%
“…[2] They have also provided evidence,i ns ome cases,f or ac oncerted mechanism in these reactions;w hereas in other cases,the formation of acarbocation intermediate was found to be favored. [2][3][4] Numerous reports of enantioselective variants of traditional halofunctionalization reactions exploit this classic reaction manifold. [2,5,6] Ty pically,such enantioselective transformations proceed through activation of the electrophilic halogen source with achiral Lewis acid [7][8][9] or hydrogen-bond donor/acceptor, [10][11][12] or through the formation of ac hiral electrophilic halogenating reagent in situ.…”
mentioning
confidence: 99%
“…Tr aditional halofunctionalization reactions proceed reliably through the formation of halonium ions,which form through nucleophilic attack at an electrophilic halogen by an alkene. [2][3][4] Numerous reports of enantioselective variants of traditional halofunctionalization reactions exploit this classic reaction manifold. Recent efforts by the Borhan research group have also suggested ar ole for the nucleophile in activating alkenes,s pecifically in chlorolactonization reactions.…”
mentioning
confidence: 99%